1994
DOI: 10.1210/endo.134.6.7515002
|View full text |Cite
|
Sign up to set email alerts
|

Cellular localization and regulation of gene expression for components of the insulin-like growth factor ternary binding protein complex.

Abstract: Insulin-like growth factors (IGFs) are present in the circulation, largely as part of a high mol wt complex including IGF-binding protein-3 (IGFBP-3) and an acid-labile subunit (ALS). This study used in situ hybridization to investigate the cellular sites of synthesis of these factors in the rat and to evaluate changes in transcript levels during development and after hypophysectomy and GH treatment. IGFBP-3 transcripts are considerably more abundant and widely expressed than ALS at birth, but both are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
2
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(82 citation statements)
references
References 11 publications
5
73
2
2
Order By: Relevance
“…22 Most circulating IGFs are produced by hepatocytes in response to growth hormone stimulation. [23][24][25] Circulating IGFBP-3 is produced by hepatic endothelium and Kupffer cells. 24,25 A number of in vitro and in vivo studies have demonstrated that IGF-I is an effective mitogen in normal epithelial cells and has strong antiapoptotic effects on breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Most circulating IGFs are produced by hepatocytes in response to growth hormone stimulation. [23][24][25] Circulating IGFBP-3 is produced by hepatic endothelium and Kupffer cells. 24,25 A number of in vitro and in vivo studies have demonstrated that IGF-I is an effective mitogen in normal epithelial cells and has strong antiapoptotic effects on breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Circulating IGFBP-3 is produced by hepatic endothelium and Kupffer cells. 24,25 A number of in vitro and in vivo studies have demonstrated that IGF-I is an effective mitogen in normal epithelial cells and has strong antiapoptotic effects on breast cancer cells. 22,26 -28 However, the effect of IGF-I may be modulated by IGFBP-3 in circulation because most of the IGF-I is bound to IGFBP-3 and once bound it is not in its active form.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the majority of the circulating IGFs are bound to IGFBP-3, which is produced mainly in the liver (32). IGFBP-3 inhibits IGF activity at the cellular level by binding competitively to IGFs and, thereby, preventing their binding to the IGF receptors in the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…It is highly expressed by the liver and other extrahepatic tissues. 5 IGF-II has a lower growth hormone dependency compared to IGF-I. The highest concentrations could be found during the fetal development.…”
mentioning
confidence: 90%